The role of formal characteristics in harmony townscape - Taher, Asma Niazy; Hussen, Ali mosa; Al musawi, Ahmad hussain (Iraqi Journal of Architecture and Planning, 2018)
this research deals with how to deal with the formal elements constituting the urban scene and its formal characteristics to achieve the phenomenon of harmony in urban centers through the construction ofan integrated theoretical model for the phenomenon of ( harmony ) , it is determined through the basics and fundamentals of harmony and the main factors that depend on it and finding the values the formal characteristics of harmony and the degrees of harmony, and according to this perspective have been identified ,the major problem of the research is: the lack of clarity of the role of the formal characteristics of the elements of the formal components of the elevation in achieving harmony in townscape, so the goal of research is to: building theoretical framework for the phenomenon of harmony in the townscape in its comprehensive concept, and the most important results of the research to build a clear structure based on an inclusive concept of all factors and vocabulary influencing the phenomenon, the phenomenon of harmony is represented with the total characteristics of the formal elements of townscape at thelevel of the part and the whole, Each elementdepends on the total variables affecting them. Key words : Harmony , Townscape ,The holy city of Najaf , formal characteristics